Asymmetric Ni-Catalyzed Radical Relayed Reductive Coupling - Wei, Xiaofeng; Shu, Wei; García-Domínguez, Andrés; Merino, Estíbaliz; Nevado, Cristina (Journal of the American Chemical Society, 2020)
Alkene dicarbofunctionalizations enable the streamlined construction of aliphatic structures and have thus been the subject of intense research efforts. Despite significant progress, catalytic asymmetric variants remain scarce. Inspired by the advantages of reductive cross-coupling approaches, we present here a highly efficient asymmetric intermolecular Ni-catalyzed reductive dicarbofunctionalization of alkenes. Two distinct readily available electrophiles, namely, Csp2- and Csp3-halides, are added simultaneously across a variety of olefins (vinyl amides, vinyl boranes, vinyl phosphonates) at room temperature in a highly regio- and enantioselective manner. The reaction, devoid of sensitive organometallic reagents, takes advantage of an in situ generated chiral alkyl Ni(III)-intermediate to ensure a stereodefined outcome in the Csp3–Csp2 bond-forming reaction. An (l)-(+)-isoleucine chiral bisoxazoline ligand and the presence of coordinating sites on the alkene are key for the successful outcome in these “asymmetric radical relayed reductive couplings” (ARRRCs). Further, multiple transformations of the chiral amides obtained in this process showcase the potential of this new methodology for the straightforward assembly of chiral building blocks such as primary and secondary amines and oxazolines, highlighting its synthetic utility.